Simvastatin ameliorates deep vein thrombosis in rabbits by regulating the fibrinolytic system. Issue 5 (July 2016) - Feng, Yaping; Zhang, Fuxian; Niu, Luyuan; Zhang, Mingyi
Abstract : The study aimed to observe the therapeutic effect of simvastatin in a deep vein thrombosis (DVT) animal model and conduct a preliminary study into its mechanism. A total of 72 New Zealand white rabbits were randomly divided into control group ( n  = 18), low molecular weight heparin (LMWH) group ( n  = 18), simvastatin group ( n  = 18), and simvastatin + LMWH group ( n  = 18). A posterior vena cava thrombus model was established and interventions were administered according to the group procedures. Blood plasma was sampled before and 3, 7, and 14 days after the intervention when the vena cava (including thrombus) specimen was collected. Specimens were weighed, histopathologically examined, and monitored for changes in venous wall inflammation. Concentrations of P-selectin, plasminogen activator inhibitor (PAI-1), and the urokinase plasminogen activator (u-PA) activity were measured with enzyme-linked immunosorbent assay. P-selectin expression in the venous wall was measured with immunohistochemistry, and quantitative PCR detected the changes of local PAI-1/u-PA expression. Simvastatin and LMWH reduced the weight of the thrombus and promoted thrombus dissolution. Simvastatin significantly inhibited the systemic and local expression of P-selectin, whereas LMWH was inhibitory only at the late stage of the acute phase. Plasma active concentration and local gene expression of PAI-1 was inhibited by simvastatin, whereas for u-PA; it was promoted at the early stage of the acute phase, but inhibited in the late stage. Simvastatin inhibited the expression of inflammatory mediators, reduced the DVT inflammatory response, alleviated inflammatory injury and reduced thrombus formation. Simvastatin may provide a beneficial adjuvant therapy for DVT. Abstract : Supplemental Digital Content is available in the text